PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI CAHAYA MAKMUR MENGGUNAKAN METODE PEMBELAJARAN AKTIF YANG DAPAT MENINGKATKAN MOTIVASI SISWA DALAM BELAJAR DAN MENGEMBANGKAN KARAKTERNYA - Aini, Nun; Sri Hasanah; Siti Patimah; M. Makhrus Ali; Siti Afifatun; Meilisa Sajdah (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Islamic Religious Education has an important role in shaping character and increasing students' learning motivation from an early age. At SD Negeri Cahaya Makmur, the application of active learning methods is one of the innovative strategies to achieve this goal. This method places students as the main subjects in the learning process, encourages active participation, group discussions, problem solving, and reflection of religious values ​​in everyday life.This research examines the effectiveness of implementing active learning methods to increase student motivation and character development in Islamic religious education. Using a qualitative descriptive approach, research was conducted at Chahaya Makmur Elementary School, including learning observations for one semester, in-depth interviews, and documentation. The research results show that the use of active learning methods such as role-playing, storytelling, and project based learning increases student learning motivation by 75% and strengthens Islamic character development. In conclusion, active learning methods have proven to be effective in achieving PAI learning objectives and strengthening student character